The Impact of Probiotics and Egg Yolk IgY on Behavior and Blood Parameters in a Broiler Immune Stress Model - Rehan, Ibrahim F.; Youssef, Mohammed; Abdel-Rahman, Mootaz A. M.; Fahmy, Sohaila G.; Ahmed, Eslam; Ahmed, Ahmed S.; Maky, Mohamed A.; Diab, Hassan M.; Shanab, Obeid; Alkahtani, Saad; Abdel-Daim, Mohamed M.; Hassan, Hamdy; et al. (Frontiers in Veterinary Science, 2020)
: Feed additives are used frequently in variable combinations to maximize broiler productivity and consumer safety. Therefore, we evaluated the efficiency of feed additives used in four different diets, a basal diet, a probiotic (PRO-PAC®) supplement diet, an egg yolk purified immunoglobulin Y (IgY) supplemented diet, and a combination of IgY and PRO-PAC® supplement (n=15 for each group). We assessed the improvement of behavioral and hematological parameters of Ross broilers before and after an immune stress challenge using lipopolysaccharide (LPS). Behavioral as well as physiological parameters were analyzed. The standing frequency was the highest (P<0.05) in broilers supplemented with a combination of probiotics and IgY. Likewise, latency approach score to a novel object improved (P<0.01) in the combination group at week-3. After intraperitoneal injection of LPS, this combination group achieved the best gait score at week-3, followed by week-5, compared to birds fed the basal diet. The Heterophil/ Lymphocyte (H/L) ratio, heterophil differential count, and eosinophil differential count in the basal diet group that was challenged with LPS were significantly increased (P< 0.01, P< 0.001, P< 0.05, respectively) compared to the combination groups. Therefore, we concluded that the combination of IgY and probiotics can significantly improve the behavior and the underlying physiological parameters of Ross broilers that are directly related to broiler production and the safety of the consumer’s diet.